The Role of Islamic Financial Institutions for UMKM During the Covid -19 Pandemic - Hasyim; Anggrini Manullang; Rian Pasaribu; Rizsa Nabillah (Indonesian Journal of Advanced Research, 2023)
Bank Syariah Indonesia carries out the bank's function as a place to store and channel funds from the public to assist development in Indonesia. The existence of a bank is also very dependent on public trust. The higher the public trust, the higher the public awareness to save their money in the bank and use other services from the bank. Small and Medium Enterprises (UMKM) are one of the main driving forces in the development of the manufacturing industry. The movement of the UMKM sector is very important to create economic growth and employment. This study aims to determine the role of Islamic banking in UMKM during the Covid-19 pandemic. This study uses a qualitative descriptive method and the data used is primary data. The instrument used in primary data is interviews. From this research it can be seen that People's Business Credit (KUR) encouraged UMKM players during the Covid-19 pandemic, by helping customers who had received disbursement of financing before the pandemic by providing relaxation or relief in paying installments.